SPECIFIC CHARACTERISTICS OF USING INTEGRATED TECHNOLOGIES IN THE EDUCATIONAL SYSTEM - N.N. Berdigulova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: this thesis provides information about the specific features of the use of integrated technologies in the educational system.